Evaluasi Kajian Oil Extraction Rate (OER) Optimum sebagai Standar Panen Kelapa Sawit - Kumbara, Kumbara; Firlana, Firlana; Supriatna, Jajang (Jurnal Agro Industri Perkebunan, 2024)
This research aims to carry out a basic evaluation of the harvest of palm kernel 3 (BD3), palm kernel 7 (BD7), fraction 1 (FR1), and fraction 2 (FR2) on the types of soil and peat and minerals that are tested and analyzed based on observations of the number of loose fruits from bunches (brondolan) on the plate. This research was conducted at PT Gandaera Hendana, Ukui 2 Village, Ukui District, Pelalawan Regency, Riau Province. The study used a factorial randomized block design (RBD) with two factors:  harvest base and two types of soil. The parameters observed consisted of adding a number of brondolan after harvest, the multiple of brondol after harvest, oil to bunch analysis, and potential oil extraction rate (OER). The analysis showed that adding loose fruit after harvest in mineral soil increased significantly two times more than peat (15.2 loose fruit). The harvest standard for fraction 2 increased significantly due to the addition of loose bunches after harvest (23.9 bunches) and their interaction in mineral soil (38.6 bunches). The base of palm kernels 3 (BD ​​3) shows a very significant increase in the yield of palm kernels after harvest (2.4 times) as well as its interaction in mineral soil (2.7 times). The palm kernels harvest standard 3 showed the highest increase in OER potential (23.25%) and OER potential in mineral soil (24.46%).